2017
DOI: 10.22159/ajpcr.2017.v10s5.23107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zidovudine Combination and Tenofovir Combination on the Effectiveness of Therapy and Side Effects in Hiv/Aids Patients in Rsal Mintohardjo

Abstract: Objectives: Tenofovir-based therapy is a newly adopted first-line HIV/AIDS therapy regimen in Indonesia that is replacing the stavudine-based regimen. However, zidovudine-based regimens remain the first-line therapy for patients with HIV/AIDS. This study aimed to compare the effectiveness and incidence of adverse effects with hemoglobin (Hb) in both zidovudine-and tenofovir-based regimens in HIV/AIDS patients at Mintohardjo Hospital. Methods:We used a cross-sectional comparative research design. The data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This might be because AZT-3TC-NVP is taken twice per day (drug burden) that results in the patient not taking the drug appropriately and end up with LTFU and also TDF-3TC-EFV is fixed-dose combinations of ART agents which helps to reduce dosing complexity [45]. Tenofovir regimen is claimed to have a better safety profile, even though it may result renal toxicity, compared to zidovudine because of a reduced incidence of anemia and fat redistribution [46][47][48][49][50], so patients with AZT-3TC-NVP may have a loss of hope on the medication if they become ill due to anemia and other complications and finally may be lost from HIV care [32].…”
Section: Discussionmentioning
confidence: 99%
“…This might be because AZT-3TC-NVP is taken twice per day (drug burden) that results in the patient not taking the drug appropriately and end up with LTFU and also TDF-3TC-EFV is fixed-dose combinations of ART agents which helps to reduce dosing complexity [45]. Tenofovir regimen is claimed to have a better safety profile, even though it may result renal toxicity, compared to zidovudine because of a reduced incidence of anemia and fat redistribution [46][47][48][49][50], so patients with AZT-3TC-NVP may have a loss of hope on the medication if they become ill due to anemia and other complications and finally may be lost from HIV care [32].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary tuberculosis (47.8%) followed by oral candidiasis (43.9%), and toxoplasmosis (10.3%) were the most frequently observed OIs. Previous studies also reported the most prevalent OIs were pulmonary tuberculosis followed by oral candidiasis [2,12,[17][18][19][20][21]. Oral candidiasis was previously reported as the most prevalent OI fungal in PLWHA due to severe suppression of the immune system [22].…”
Section: Iv: Intravenousmentioning
confidence: 93%
“…People living with HIV/AIDS (PLWHA) often appears with many comorbidities and stigma from their community [2][3][4]. PLWHA must face the disease caused by HIV infection itself or iatrogenic due to the treatment [5]. Hence, HIV/AIDS gives an increasing health burden that causing several socioeconomic problems for the patient, family, community, and government [1][2].…”
Section: Introductionmentioning
confidence: 99%